Ciri Kebahasaan Teks Laporan Hasil Observasi Siswa Kelas X SMA Negeri 1 Enam Lingkung - Paramita, Novia; Zulfikarni, Zulfikarni (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2023)
This study aims to describe the characteristics of the language of the observation report text and the errors found in the characteristics of language contained in the text of the observation report of students of class X of State High School 1 Enam Lingkung. This type of research is qualitative research with descriptive methods by analyzing the use of language characteristics from the text of the report of the observations of students of class X of State High School 1 Enam Lingkung. Based on the results of the study, it was concluded that in this study on the characteristics of the language of the text of the observation report which includes repetition, pronomina, conjunctions, and defenisi sentences in the text of the report of observation of the work of students of class X state high school 1 Six Lingkung is good enough. However, there are still text observation reports that do not meet the characteristics of language contained in the text of the observation report.